Alginate/bacterial cellulose nanocomposite beads prepared using Gluconacetobacter xylinus and their application in lipase immobilization. (10th February 2017) - Kim, Ji Hyun; Park, Saerom; Kim, Hyungsup; Kim, Hyung Joo; Yang, Yung-Hun; Kim, Yong Hwan; Jung, Sang-Kyu; Kan, Eunsung; Lee, Sang Hyun
Highlights: Alginate/bacterial cellulose (BC) beads with well-controlled size and shape were prepared. Alginate/BC beads showed high surface area, high crystallinity, and high water-holding capacity. Alginate/BC beads were more favorable than alginate beads for lipase immobilization. Alginate/BC beads have many potential applications in biocatalytic, biomedical, and pharmaceutical fields. Abstract: Alginate/bacterial cellulose nanocomposite beads, with well-controlled size and regular spherical shapes, were prepared in a simple manner by entrapping Gluconacetobacter xylinus in barium alginate hydrogel beads, followed by cultivation of the entrapped cells in culture media with a low sodium ion concentration. The entire surface of the alginate hydrogel beads containing the cells was covered with cellulose fibers (∼30 nm) after 36 h of cultivation. The cellulose crystallinity index of the alginate/bacterial cellulose beads was 0.7, which was slightly lower than that of bacterial cellulose prepared by cultivating dispersed cells. The water vapor sorption capacity of the alginate/bacterial cellulose beads increased significantly from 0.07 to 38.00 (g/g dry bead) as cultivation time increased. These results clearly indicate that alginate/bacterial cellulose beads have a much higher surface area, crystallinity, and water-holding capacity than alginate beads. The immobilization of lipase on the surface of the nanocomposite beads was also investigated as a potential application of this system. The activity and specific activity of lipase immobilized on alginate/bacterial cellulose beads were 2.6- and 3.8-fold higher, respectively, than that of lipase immobilized on cellulose beads. The alginate/bacterial cellulose nanocomposite beads prepared in this study have several potential applications in the biocatalytic, biomedical, and pharmaceutical fields because of their biocompatibility, biodegradability, high crystallinity, and large surface area.